The Port of Manzanillo from the Point of View of Economy of Organization - Vargas-Hernández, José; Lopez-Morales, Jose Satsumi; Cruz, Irving Daniel Agustín (JPAIR Multidisciplinary Research, 2016)
Globalization has become a trigger factor in international trade due to its role as an integral part of the world economy and social standardization in the context of technological, cultural and universal knowledge which allows free access to resource with minimal effort. The study is a contribution to theories based on the Industry, the Dynamic Resources and Institutions; all around the Mexican Port System. Data was gathered using a qualitative approach of literature review about the current status of the ports and its global environment. The results were organized around the statement of the problem and research objective that guide the study. The results indicated that Manzanillo Port holds dynamic capabilities that increase its competitiveness in the global port industry as strategic locations, and its natural and human resources.